Manajemen Program Pendidikan di Pesantren Mahasiswi Darul Arifin II Jember - Faridatul Jannah; Siti Aminah (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2020)
The purpose of this study is to know how the planning, organization, implementation, and supervision of the education program at Darul Arifin II Islamic Boarding School. This study belongs to field research by doing qualitative approach. The data is obtained by observation, interviews, and documentation techniques. The data analysis is done by data condescension, data display and conclusion drawing. The data are validated through sources and techniques triangulation. The results of this study are: 1) The planning of educational programs is done by setting goals, formulating present circumstances, identifiying ease and obstacles, and developing plans into long-term and short-term programs. 2)The organization of educational programs includes division of work, departementalization, and range of control. 3) The implementation of the educational programs is basically two programs, a routine and incidental programl. The routine program consists of yellow book education programs, development of foreign languages, tahfidz and tahsin al-Qur'an. Whereas the incidental program consisted of the education program of the dzikir and sholawat groups, and the strengthening of the Aswaja. 4) Educational programs are supervised by setting standards, measuring work performance, adjusting work perfomance to standards, and taking corrective measures. Tujuan penelitian ini untuk mengetahui bagaimana prencanaan, pengorganisasian, pelaksanaan, dan pengawasan program pendidikan di Pesantren Mahasiswi Darul Arifin II. 1) Perencanaan dilakukan dengan cara menetapkan tujuan, merumuskan keadaan sekarang, mengidentifikasi kemudahan dan hambatan, dan mengembangkan rencana ke dalam program jangka panjang dan program jangka pendek. 2) Pengorganisasian program pendidikan meliputi pembagian kerja, departementalisasi, dan rentang kendali. 3) Pelaksanan program pendidikan pada dasarnya terdapat dua program yaitu program rutinitas dan insidentil. Program rutinitas ini terdiri dari program pendidikan kajian kitab kuning, pengembagan bahasa asing, tahfidz dan tahsin al-Qur’an. Sedangkan program insidentil terdiri dari program pendidikan majelis dzikir dan sholawat, dan penguatan aswaja. 4) Pengawasan program pendidikan dilakukan dengan menetpkan standar, mengukur prestasi kerja, menyesuaikan prestasi kerja dengan standar, dan mengambil tindakan korektif. Kata Kunci: manajemen program pendidikan, pesantren mahasiswa